ijsr 2021
DOI: 10.36106/0902837
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Causes of Neonatal Jaundice in a Population of North East India

Abstract: Background: Neonatal jaundice is a common cause of mortality and morbidity in newborn babies and account for up to 60% cases in term and 80% in preterm babies. Studies from different geographical areas should be done to know the causes of hyperbirubinemia properly so that a collective effort can be made to decrease the burden mortality and morbidity associated with it Objectives:To study the incidence and causes of neonatal jaundice in babies admitted in the hospital Methods: It was a hospital based observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Although we got patients mostly due to exaggerated physiological jaundice, other causes are not negligible. [25][26] Regarding the outcome, we found that babies with blood group incompatibilities required longer duration of phototherapy. Study done by Bhat YR also concluded from their study that neonates with hemolysis required phototherapy significantly earlier and for longer than neonates without hemolysis (P<0.001).…”
Section: Resultsmentioning
confidence: 87%
“…Although we got patients mostly due to exaggerated physiological jaundice, other causes are not negligible. [25][26] Regarding the outcome, we found that babies with blood group incompatibilities required longer duration of phototherapy. Study done by Bhat YR also concluded from their study that neonates with hemolysis required phototherapy significantly earlier and for longer than neonates without hemolysis (P<0.001).…”
Section: Resultsmentioning
confidence: 87%